2012
DOI: 10.1093/infdis/jis336
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Protects Mice From Staphylococcus aureus Pneumonia Via Inhibition of the Cytolytic Activity of α-Hemolysin

Abstract: α-Hemolysin (Hla) is a self-assembling, channel-forming toxin that is secreted by Staphylococcus aureus and is central to the pathogenesis of pulmonary, intraperitoneal, intramammary, and corneal infections in animal models. In this study, we report that baicalin (BAI), a natural compound that lacks anti-S. aureus activity, could inhibit the hemolytic activity of Hla. Using molecular dynamics simulations and mutagenesis assays, we further demonstrate that BAI binds to the binding sites of Y148, P151, and F153 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 36 publications
1
118
1
2
Order By: Relevance
“…Bronchoalveolar lavage (BAL) fluid collections were administered twice by intratracheal instillation of 500 ml of sterile PBS. The clear surface liquid obtained after centrifugation was collected, and the lavage fluid supernatants were used for cytokine detection (Qiu et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Bronchoalveolar lavage (BAL) fluid collections were administered twice by intratracheal instillation of 500 ml of sterile PBS. The clear surface liquid obtained after centrifugation was collected, and the lavage fluid supernatants were used for cytokine detection (Qiu et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Increasing evidence indicated that certain natural products protect mice from S. aureus pneumonia (26)(27)(28). A previous study demonstrated that resveratrol had obvious anti-bacterial activities against clinical isolates of methicillin-resistant S. aureus (29).…”
Section: Discussionmentioning
confidence: 99%
“…21,[28][29][30] Qiu et al previously reported that baicalin, a kind of flavonoid, inhibited the cytolytic activity of alpha-hemolysin by blocking the assembly of the alpha-hemolysin monomer to a heptamer and also had a protective effect against S. aureus pneumonia in a mouse model. 21) In the present study, we determined whether baicalin inhibited the activity of ALH. Our results showed that baicalin did not inhibit the activity of ALH, but was effective against that of alpha-hemolysin.…”
Section: Discussionmentioning
confidence: 99%
“…21) We tested the effect of baicalin to the hemolytic activity of ALH. However, baicalin did not inhibit the activity of ALH (Fig.…”
Section: Synthesis Of Indolo[32-b]quinoline Derivativesmentioning
confidence: 99%
See 1 more Smart Citation